2017
DOI: 10.1002/mabi.201600513
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Antimetastatic Activity of the Ruthenium Anticancer Drug RAPTA‐C Delivered in Fructose‐Coated Micelles

Abstract: (HER-2) has been utilized as a targeting site for the Trastuzumab drug delivery system. Trastuzumab is a humanized monoclonal antibody and has been widely used for HER2-positive metastatic breast cancer. [2] In the case of triplenegative breast cancer, [3] which is lacking the expression of progesterone receptor (PR), estrogen receptor (ER), and human epidermal growth factor receptor 2 (HER-2/neu), other targeting mechanism are sought after. Interestingly, an overexpression of fructose transporter GLUT5 could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…It should also be noted the use of polymer micelles for the delivery of Pt(II) and Ru(II) complexes to cancer cells. 140 Palladium catalysts were used to catalyze intracellular reactions by uncaging various model prodrugs, including the doxorubicin (DOX) prodrug (pro-DOX), for the effective tumor treatment in vivo. 141 The Pd(II) catalysts were encapsulated in the micellar core of diblock amphiphilic copolymers poly(lactic acid-co-glycolic acid) (PLGA)-PEG, which were intravenously delivered to various tumor cell models using the enhanced permeability and retention (EPR) effect.…”
Section: Metal-containing Synthetic Polymersmentioning
confidence: 99%
“…It should also be noted the use of polymer micelles for the delivery of Pt(II) and Ru(II) complexes to cancer cells. 140 Palladium catalysts were used to catalyze intracellular reactions by uncaging various model prodrugs, including the doxorubicin (DOX) prodrug (pro-DOX), for the effective tumor treatment in vivo. 141 The Pd(II) catalysts were encapsulated in the micellar core of diblock amphiphilic copolymers poly(lactic acid-co-glycolic acid) (PLGA)-PEG, which were intravenously delivered to various tumor cell models using the enhanced permeability and retention (EPR) effect.…”
Section: Metal-containing Synthetic Polymersmentioning
confidence: 99%
“…Next, Martina Stenzel and co‐workers report the application of fructose‐coated micelles to overcome the poor delivery efficiency of the ruthenium complex dichlororuthenium (II) p ‐cymene (1,3,5‐triaza‐7‐phosphaadamantane) in tumor spheroid models and invasion assays. The reported results demonstrate the potential of polymeric micelles to enhance bioavailability of poorly soluble drugs and underline the role of carbohydrates for enhancing cellular uptake …”
mentioning
confidence: 58%
“…5 Recently, glycopolymer-coated nanoparticles have attracted great interest due to the specific binding between them and carbohydrate receptors located on the cancer cell surface, suggesting that these synthetics are potential to deliver agents into tumor cells in a targeted way [13]. Several studies have addressed that the intake of FCN can be substantially observed in tumor cells but rarely in healthy cells [13,41], which is correlated to the overexpressed GLUT5 found on the surface of tumor cells [42,43]. Of note, nanoparticles that are coated with hydrophilic shell manufactured by long polymer chains with high fructose density have great affinity to tumor cells [14].…”
Section: Discussionmentioning
confidence: 99%